2016
DOI: 10.7717/peerj.2572
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of the tropical earthwormPontoscolex corethrurus(Rhinodrilidae, Oligochaeta) in temperate grasslands

Abstract: The tropical earthworm Pontoscolex corethrurus (Rhinodrilidae, Oligochaeta) presents a broad distribution (e.g., 56 countries from four continents). It is generally assumed that temperature appears to limit the success of tropical exotic species in temperate climates. However, the distribution range of this species could advance towards higher elevations (with lower temperatures) where no tropical species currently occur. The aim of this study was to evaluate the soil and climatic variables that could be close… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…The map shows that it is present not only in tropical regions but also in sub-tropical zones. For instance, Ortiz-gamino et al (2016) recorded its presence in sub-tropical regions of Mexico, at an elevation of 1550-1619 m above sea level (m.a.s.l. ), and an average temperature of 17°± 2, where no other tropical species occur.…”
Section: Distribution and Dispersal Vectorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The map shows that it is present not only in tropical regions but also in sub-tropical zones. For instance, Ortiz-gamino et al (2016) recorded its presence in sub-tropical regions of Mexico, at an elevation of 1550-1619 m above sea level (m.a.s.l. ), and an average temperature of 17°± 2, where no other tropical species occur.…”
Section: Distribution and Dispersal Vectorsmentioning
confidence: 99%
“…Its abundance is positively affected by organic matter availability Marichal et al, 2010;Ortiz-Gamino et al, 2016), N availability (Li et al, 2010;Marichal et al, 2010) and P availability (Marichal et al, 2011) in the soil. Therefore, this morphospecies prefers rich soils in terms of organic matter and leaf litter (Liu and Zou, 2002;Ganihar, 2003;García and Fragoso, 2003).…”
Section: Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…Sales [18] observed that in the dry season the soil is more resistant to the deformations caused by the movement of earthworms since a costly effort would be necessary to move through the soil profile. In a study on earthworms in temperate areas, Ortiz-Gamino et al [19], points out that along an altitudinal gradient, the climate can act as a barrier to the distribution of earthworms, and its abundance occurs in a significant way through soil fertility and pasture quality.…”
Section: Resultsmentioning
confidence: 99%